Exclusive corporate philanthropy: rethinking the nexus of CSR and corporate philanthropy. Issue 2 (6th June 2016) - von Schnurbein, Georg; Seele, Peter; Lock, Irina
Abstract : Purpose: The purpose of this paper is to add to a better understanding of relationship of corporate social responsibility (CSR) and corporate philanthropy. The authors argue that corporate philanthropy is exclusive to CSR because of their different characteristics. Design/methodology/approach: This paper is based on a profound literature review and discusses the relationship of CSR and corporate philanthropy from a theoretical point of view. By conceptually combining the CSR pyramid and the triple bottom line approach, the authors show that corporate philanthropy has a special role outside of the classical CSR concept. Findings: Four fundaments of corporate philanthropy – economic, motivational, creative and moral – are described that illustrate the importance and outstanding role of corporate philanthropy for today's businesses. Based on these, the authors formulate three new forms of corporate giving, volunteering and foundations, which the authors subsume under the novel notion of "exclusive corporate philanthropy". Research limitations/implications: The main contribution of this paper for future research is to regard corporate philanthropy as exclusive to CSR. Future studies might, therefore, consider the different characteristics of corporate philanthropy and engage in an empirical investigation of this new type. Practical implications: The model of exclusive corporate philanthropy presented in this paper provides practitioners with a better understanding of how corporate philanthropy can be rolled out today. Originality/value: This paper offers a new perspective on the relationship of CSR and corporate philanthropy. Based on the economic, motivational, creative and moral characteristics of corporate philanthropy, the authors establish a clear distinction between the two concepts.